Building a Secure Decentralized Energy System with Remote Monitoring Using Mobile Agents - Eldegwi, H. M.; Badawy, M. B.; Kelash, Hamdy M. (2015 Fifth International Conference on e-Learning (econf), 2015)
Centralized systems have failed in remote rural areas due to weak infrastructures, roads between urban habitations are in a very bad condition even if found, scattered communities and high losses, this makes grid extension not feasible from financial point of view. Decentralized-energy system (DES) is considered the most successful types of rural electrification solutions, especially in emerging countries. Decentralized energy system plans a significant role for developed countries in attenuating risks and security threats of the electricity sector and guarantee continuous electricity distribution in times of natural disasters and attacks. In fact, only decentralized energy supply system can't mitigate with the risk associated with a centralized electricity sector especially in remote rural areas. Therefore, it is urgently required to build a secure model of decentralized energy system integrated with information system for remote monitoring based on mobile agents (MA), and incorporates (RC5) algorithm into the system because of its exceptional simplicity which makes it easy to implement and analyze operational data remotely.